Efficacy of selected botanical extracts against Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) on tomato - Nabutse, Daniel Kepha; Saidi, Mwanarusi; Ogweno, Joshua (International Journal of Horticultural Science, 2025)
Tuta absoluta Meyrick, also known as the tomato leaf miner, is a destructive pest that feeds on tomato plants, causing significant economic losses to tomato farmers globally. Traditional methods of controlling Tuta absoluta involve the use of synthetic pesticides, but these methods have drawbacks such as environmental pollution, development of resistance by the pest, and negative effects on non-target organisms. As a result, there is a growing interest in the use of botanical extracts as alternative and safer pest control options. Three bioassay experiments were conducted to test the insecticidal, antifeedant and repellency effects of botanical extracts on Tuta absoluta. The experiments were conducted as completely randomized design (CRD) with three (3) replicates. There were eleven treatments; pyrethrum, neem, warbugia, each at different concentration levels of (8%, 10%, 12%) and controls positive (Indoxacarb 150g/L) and negative (distilled water). In all the bioassay conducted, the effects of all treatments increased over time, except for distilled water control. Synthetic chemical Indoxacarb exhibited significantly stronger insecticidal properties compared to neem, warburgia and pyrethrum extracts. Application of neem at 8%, 10% and 12% and pyrethrum at 12% had higher antifeeding effect on Tuta absoluta compared to the other treatments while warburgia at 8% concentration and indoxacarb had the lowest repellency effect compared to the other plant extracts.